Pengaruh Pembangunan Jalan Lingkar Luar Petuk Terhadap Perubahan Fungsi Kawasan Dan Kondisi Sosial Ekonomi Masyarakat Di Kota Kupang - Widodo, Muh (Bumi Lestari; Vol 23 No 1 (2023)DO - 10.24843/blje.2023.v23.i01.p02, 2022)
The construction of the Petuk Outer Ring Road in Kupang City is one of the national priority projects and is a new icon in the city of Kupang. The construction of the Petuk Outer Ring Road has a more or less effect on changes in the function of the area and the socio-economic conditions of the surrounding community. In terms of physical changes in the function of the area, one of which is marked by changes in land use around the Petuk outer ring road which is dominated by the emergence of new settlements with a growth rate of 13.475 ha or 0.56% per year, while changes in the socio- economic conditions of the community are indicated by the emergence of new types of business, a change in the type of work (non-agricultural) and an increase in the selling price of land